Strategies for integrating and teaching soft skills in institution of learning - Akinbode, Akintola Ismaila; Al-Shuhumi, Said Rasheed Ali; Al-Hidabi, Dawood Abdulmalek Yahya (University of Ilorin, Nigeria, 2023)
The whole world is facing unprecedented changes in social, educational, economic, and environmental sectors. The changes, coupled with advanced technological development, have ushered in challenges and opportunities, as well as changed human endeavors and relationships. Institutions of learning, where the manpower of a nation is produced, therefore have to brace up to prepare future-ready students who will be able to navigate through these arrays of complex societal problems, find untapped opportunities, influence people and circumstances, form mutually supportive and effective relationships, and create new values and ideas. For students to position themselves well and significantly contribute in this VUCA (volatile, uncertain, complex, and ambiguous) world, they need a variety of skills, including metacognitive skills (problem solving, creativity, and critical skills), social and emotional skills (communication, collaboration, empathy, and digital skills), in conjunction with hard or technical skills that are majorly focused on by the schools. Thus, institutions of learning have to equip students with soft skills so that they can match up with future requirements and competencies needed in a changing world. This paper discusses the meaning and importance of soft skills and how they can be integrated into the curriculum and taught in schools.